2019
DOI: 10.1111/jphd.12350
|View full text |Cite
|
Sign up to set email alerts
|

Dental professionals' knowledge, attitudes, and practice behaviors related to human papillomavirus vaccination

Abstract: Objectives In Arizona, human papillomavirus (HPV)‐related cancers are declining, with the exception of oropharyngeal cancer (OPC). HPV‐related OPC is largely caused by persistent infection with oncogenic HPV strains, many of which the 9‐valent HPV vaccine offers protection. Little is known about dental professionals' willingness to promote the HPV vaccine to prevent OPC. The current study assessed Arizona dental professionals' knowledge, attitudes, willingness, and current practice behaviors related to HPV vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 21 publications
9
35
0
Order By: Relevance
“…On the other hand, the rate of participants indicating that HPV will recover spontaneously was found to be extremely low in the present study. This result is also compatible with the results of Patel et al (10). Regarding the question about HPV's absence of obvious signs, the majority of dentists in Patel et al's study (10) responded correctly, but in our study, the correct response rate was lower for both dentists and students.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the rate of participants indicating that HPV will recover spontaneously was found to be extremely low in the present study. This result is also compatible with the results of Patel et al (10). Regarding the question about HPV's absence of obvious signs, the majority of dentists in Patel et al's study (10) responded correctly, but in our study, the correct response rate was lower for both dentists and students.…”
Section: Discussionsupporting
confidence: 92%
“…Dentists have an important role in OPC screening, diagnosis, awareness, and patient education. Although the general risk factors of cancers in the oral region are well known, information about the role of viruses in oral cancer risk is unclear (10). The relationship between HPV and OPC has been revealed recently (3,9,10,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few previous studies that evaluated the awareness, knowledge and acceptance of HPV vaccination among dental students and post-graduate residents found deficiencies in both knowledge and awareness [15][16][17][18]. This study evaluated both dental student and post-graduate resident awareness, knowledge and acceptance of HPV vaccination during a curricular module devoted to immunization practices and HPV-specific vaccination and found noteworthy similarities and differences.…”
Section: Discussionmentioning
confidence: 87%
“…Although a few studies have evaluated knowledge or awareness of HPV vaccination among practicing dentists or dental educators, it is unclear whether this information receives sufficient emphasis in dental education to mold student views on vaccination that lead to their implementation by students when they enter dental practice. Few studies have evaluated the awareness, knowledge and acceptance of HPV vaccination among dental students and post-graduate residents [15,16]. The few studies to date that have evaluated dental students specifically, have found deficiencies in both knowledge and awareness that may be addressed through changes to the dental curriculum [17,18].…”
Section: Introductionmentioning
confidence: 99%